Multi-omic single cell analysis resolves novel stromal cell populations in healthy and diseased human tendon - Kendal, AR; Layton, T; Al-Mossawi, H; Appleton, L; Dakin, S; Brown, R; Loizou, C; Rogers, M; Sharp, R; Carr, A (Springer Nature, 2020)
Tendinopathy accounts for over 30% of primary care consultations and represents a growing healthcare challenge in an active and increasingly ageing population. Recognising critical cells involved in tendinopathy is essential in developing therapeutics to meet this challenge. Tendon cells are heterogenous and sparsely distributed in a dense collagen matrix; limiting previous methods to investigate cell characteristics ex vivo. We applied next generation CITE-sequencing; combining surface proteomics with in-depth, unbiased gene expression analysis of > 6400 single cells ex vivo from 11 chronically tendinopathic and 8 healthy human tendons. Immunohistochemistry validated the single cell findings. For the first time we show that human tendon harbours at least five distinct COL1A1/2 expressing tenocyte populations in addition to endothelial cells, T-cells, and monocytes. These consist of KRT7/SCX+ cells expressing microfibril associated genes, PTX3+ cells co-expressing high levels of pro-inflammatory markers, APOD+ fibro–adipogenic progenitors, TPPP3/PRG4+ chondrogenic cells, and ITGA7+ smooth muscle-mesenchymal cells. Surface proteomic analysis identified markers by which these sub-classes could be isolated and targeted in future. Chronic tendinopathy was associated with increased expression of pro-inflammatory markers PTX3, CXCL1, CXCL6, CXCL8, and PDPN by microfibril associated tenocytes. Diseased endothelium had increased expression of chemokine and alarmin genes including IL33.